Reduced short-term variation following antenatal administration of betamethasone: Is reduced fetal size a predisposing factor?. (September 2017) - Ghi, Tullio; Dall'Asta, Andrea; Saccone, Gabriele; Bellussi, Federica; Frusca, Tiziana; Martinelli, Pasquale; Pilu, Gianluigi; Rizzo, Nicola
Abstract: Objective: To assess the association between fetal size and the incidence of reduced short-term variability (STV) following bethametasone administration for fetal lung maturity. Study design: This was a retrospective, multicenter, cohort study conducted in two Tertiary University Units. Only uncomplicated singleton pregnancies admitted for threatened preterm labor between 26 and 34 weeks and submitted to betamethasone for fetal lung maturity were included. Delivery occurring within 72 h from betamethasone administration represented criteria for exclusion. Computerized cardiotocography was carried out on a daily basis. Cases were identified by persistently reduced STV, defined as <5th percentile for gestational age and lasting for at least 72 h after the first dose of betamethasone. The primary outcome was estimated fetal weight (EFW) at ultrasound in fetuses with normal and in those with persistently reduced STV. Pregnancy outcomes were also evaluated. Results: Persistently reduced STV occurred in 33/405 of the included patients (8.1%). Compared to women with normal STV, those with persistently reduced STV had significantly lower EFW (1472 ± 435 vs 1812 ± 532 g, p 0.04), lower birthweight (2353 ± 635 vs 2857 ± 796 g, p < 0.01) and earlier gestational age at delivery (35.1 ± 4.2 vs 37.3 ± 2.4 weeks, p < 0.01), whereas all the other variables including gestational age on admission were comparable. Conclusions: Reduced STV following maternal betamethasone administration among appropriately grown fetuses seems to correlate with lower fetal size. Furthermore, fetuses with such abnormal response to steroids seem to carry a higher risk of perinatal complications, including lower birthweight and earlier gestational age at delivery.